Leukemia-Initiating Cells in T-Cell Acute Lymphoblastic Leukemia - Tan, Shi Hao; Bertulfo, Fatima Carla; Sanda, Takaomi (Frontiers in Oncology, 2017)
T-cell acute lymphoblastic leukemia (T-ALL) is a hematological malignancy characterized by the clonal proliferation of immature T-cell precursors. T-ALL has many similar pathophysiological features to acute myeloid leukemia, which has been extensively studied in the establishment of the cancer stem cell (CSC) theory, but the CSC concept in T-ALL is still debatable. Although leukemia-initiating cells (LICs), which can generate leukemia in a xenograft setting, have been found in both human T-ALL patients and animal models, the nature and origin of LICs are largely unknown. In this review, we discuss recent studies on LICs in T-ALL and the potential mechanisms of LIC emergence in this disease. We focus on the oncogenic transcription factors TAL1, LMO2 and NOTCH1 and highlight the significance of the transcriptional regulatory programs in normal hematopoietic stem cells and T-ALL.